2016
DOI: 10.1002/jsfa.8019
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a thermostable glycoside hydrolase (CMbg0408) from the hyperthermophilic archaeon Caldivirga maquilingensisIC‐167

Abstract: As a result of its remarkable thermostability and high activity at high temperatures, this novel β-galactosidase may be useful for food and pharmaceutical applications. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…In our previous study, a putative bgl B gene encoding for a GH1 enzyme from the hyperthermophilic Caldivirga maquilingensis strain IC‐167 was cloned and expressed in Escherichia coli . Characterization of the biochemical properties of the purified recombinant protein revealed that it possessed 100% β ‐galactosidase activity with 50% β ‐glucosidase and 25% xylosidase activities and displayed significant thermostability, suggesting that it may be useful for industrial exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, a putative bgl B gene encoding for a GH1 enzyme from the hyperthermophilic Caldivirga maquilingensis strain IC‐167 was cloned and expressed in Escherichia coli . Characterization of the biochemical properties of the purified recombinant protein revealed that it possessed 100% β ‐galactosidase activity with 50% β ‐glucosidase and 25% xylosidase activities and displayed significant thermostability, suggesting that it may be useful for industrial exploitation.…”
Section: Introductionmentioning
confidence: 99%
“…Studies focusing on transcriptomics of cultured archaea or reassembling of uncultured archaeal genomes will provide highly useful insights into new archaeal metabolisms, and novel catabolism reactions could be investigated for degradation of complex substrates [105]. [46,47], Pyrococcus horikoshii [52], Saccharolobus shibatae [65], Saccharolobus solfataricus [41], and three unknown archaea [42,81,83]; amylases of Pyrococcus furiosus [43,44,48,49], Sulfolobus acidocaldarius [67], Pyrococcus woesei [54], and Staphylothermus marinus [59]; sylanase of Saccharolobus solfataricus [69]; glucosidases of Pyrococcus furiosus [50,51], Pyrobaculum aerophilum [78] and two unknown archaea [22,40]; galactosidases of Saccharolobus solfataricus [70,71] and Caldivirga maquilingensis [76]; xylosidase of Saccharolobus solfataricus [73]; mannosidase of Saccharolobus solfataricus [74]…”
Section: Classification Of Ghs Demonstrates a Small Number Of Charactmentioning
confidence: 99%
“…[ 73 ] 90 T 1/2 38 h at 90 °C AJ251975 Mannosidase (GH 38) intracellular enzyme [ 74 ] 85 > 20% activity after 10 min at 80 °C AAK43108.1; AIX48014.1; CAC24028.1; NP_344318.1 (from CAZy website) Caldivirga maquilingensis [ 75 ] 60–92 85 Galactosidase (GH1) secretion n.l. [ 76 ] 110 100% relative activity after 120 min at 90 °C ABW01253.1 Pyrobaculum aerophilum [ 77 ] 75–104 100 Glucosidase (GH31) intracellular [ 78 ] 90 46% relative activity after 1 h at 110 °C gi:18160499 Picrophilus torridus [ 79 ] 45–65 60 Glucosidase (GH31) intracellular enzyme [ 80 ] 87 81% relative activity after 120 min at 80 °C AAT42677.1 (from CAZy website) Mannosidase (GH38) intracellular enzyme [ 80 ] 70 50% relative activity after 1 h at 80 °C (with Cd 2+) AAT42676.1 Functional screening of metagenomes derived from hydrothermal systems Metagenome Characterized GH derived from metagenome (archaeal origin) T opt [°C] T stab Genbank accession no. *** Deep sea hydrothermal vent Endoglucanase (GH 12) extracellular enzyme [ …”
Section: Discovery Of the Potential Of Archaea And Their Glycoside Hymentioning
confidence: 99%